1983
DOI: 10.1152/jn.1983.49.4.948
|View full text |Cite
|
Sign up to set email alerts
|

Descending inhibitory influences from periaqueductal gray, nucleus raphe magnus, and adjacent reticular formation. II. Effects on medullary dorsal horn nociceptive and nonnociceptive neurons

Abstract: 1. This study examined the inhibitory effects elicited by brain stem stimulation on the somatosensory responses of trigeminal medullary dorsal horn (subnucleus caudalis of the spinal trigeminal nucleus) neurons. Single-unit extracellular recordings were obtained in chloralose-anesthetized cats. Neurons were classified as wide dynamic range (WDR), nociceptive specific (NS), or low-threshold mechanoreceptive (LTM). Conditioning stimuli were delivered to the periaqueductal gray (PAG), nucleus cuneiformis (CU), nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
42
0
3

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(47 citation statements)
references
References 0 publications
2
42
0
3
Order By: Relevance
“…Because VMM stimulation modulates the cellular responses and behavioral reactions evoked by both noxious and innocuous inputs (33)(34)(35), a generalized decrease in reactivity to somatosensory stimulation may accompany feeding, allowing an animal to nourish itself without being distracted by every falling leaf or gust of wind. Taken together, our work has shown that decreases in ON cell firing and increases in OFF cell firing occur during sleep, eating, drinking, and micturition (21,22,31).…”
Section: Discussionmentioning
confidence: 99%
“…Because VMM stimulation modulates the cellular responses and behavioral reactions evoked by both noxious and innocuous inputs (33)(34)(35), a generalized decrease in reactivity to somatosensory stimulation may accompany feeding, allowing an animal to nourish itself without being distracted by every falling leaf or gust of wind. Taken together, our work has shown that decreases in ON cell firing and increases in OFF cell firing occur during sleep, eating, drinking, and micturition (21,22,31).…”
Section: Discussionmentioning
confidence: 99%
“…Spinal dorsal horn neurons are subject to modulation by the supraspinal descending pathways. For example, stimulation of the periaquaductal gray and rostral ventromedial medulla inhibits dorsal horn neurons (Dostrovsky et al, 1983;Basbaum and Fields, 1984). However, the role of the descending pathways in the analgesic effect and inhibition of ascending dorsal horn neurons produced by systemic opioids is not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…Both systemic and spinal local application of opioids produces potent analgesia and inhibition of dorsal horn neurons (Yaksh and Rudy, 1977;Sastry and Goh, 1983;Yaksh and Noueihed, 1985;Magnuson and Dickenson, 1991). The spinal dorsal horn neurons are subject to descending modulation from supraspinal sites such as the periaquaductal gray, locus coeruleus, and rostral ventromedial medulla (Dostrovsky et al, 1983;Bodnar et al, 1990;Urban and Smith, 1994;Pan et al, 2004). Some studies suggest that the analgesic effect of opioids may be mediated by descending inhibition of dorsal horn neurons (Basbaum and Fields, 1984;Wigdor and Wilcox, 1987;Chiang and Zhuo, 1989).…”
mentioning
confidence: 99%
“…Mecanismos de inibição central e periférica aparecerão em diferentes sítios cerebrais na tentativa de restabelecer este equilíbrio [13][14][15][16][17][18][19][20][21] . O tempo necessário para que isto ocorra, corresponde a duração média das crises de migrânea.…”
Section: Discussionunclassified